Bioequivalence study between two formulations of betamethasone dipropionate and betamethasone disodium phosphate injectable suspension in healthy adults - Carlos SVERDLOFF; Vinícius Marcondes REZENDE; Camila Kaori AIHARA; Vitor ENGUEL; Camila Leles GUIMARÃES; Anne Michelli SILVEIRA; Márcia Aparecida ANTÔNIO (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2024)
Objective: To evaluate bioequivalence between two formulations of 5,0 mg/mL betamethasone dipropionate + 2,0 mg/mL betamethasone disodium phosphate injectable suspension in healthy adults under fasting condition. Methods: The study was an open label, randomized, single dose, 2x2 crossover study in 36 healthy adult subjects under fasting conditions. Betamethasone concentrations in human plasma were determined using a validated liquid chromatography coupled to a tandem mass spectrometer detector method. Results: Statistical analysis has determined confidence intervals, power of the test and p-value for sequence effect to the pharmacokinetic parameters Cmax, AUC0-t and AUC0-∞. The geometric mean ratio (90%CI) of the test drug/reference drug for betamethasone were 87.74% to 92.23% for Cmax, 93.95% to 98.91% for AUC0-t and 94.36% to 99.95% for AUC0-∞. Power of the test was 100% for all parameters and p-value for sequence effect were 33.39% for Cmax, 19.98% AUC0-t, and 24.32% for AUC0-∞. Conclusion: Reference and test formulations are statistically bioequivalent and, therefore, interchangeable, according to the local and international criteria, since confidence intervals for Cmax and AUC0-t ratios were within 80% and 125%, according to Anvisa resolution RE nº 1170/2006.